Derechos humanos y migración: manual de sanciones y debido proceso en materia migratoria en Colombia (2020)
This manual is a tool that seeks to present in clear language some concepts that foreigners in Colombian territory should be aware of (rights of migrants, international law instruments and organizations, types of sanctions in migration issues, due process, among others). The purpose is to empower all migrants who require it, through knowledge of the rights they have and how to exercise them.--Taken from the Degree Document Format.